Recombinant BCG expressing the LTAK63 adjuvant increased memory T cells and induced long-lasting protection against Mycobacterium tuberculosis challenge in mice - Marques-Neto, Lázaro Moreira; Trentini, Monalisa Martins; Kanno, Alex Issamu; Rodriguez, Dunia; Leite, Luciana Cezar de Cerqueira (Frontiers in Immunology, 2023)
Vaccine-induced protection against Mycobacterium tuberculosis (Mtb) is usually ascribed to the induction of Th1, Th17, and CD8 + T cells. However, protective immune responses should also involve other immune cell subsets, such as memory T cells. We have previously shown improved protection against Mtb challenge using the rBCG-LTAK63 vaccine (a recombinant BCG strain expressing the LTAK63 adjuvant, a genetically detoxified derivative of the A subunit from E. coli heat-labile toxin). Here we show that mice immunized with rBCG-LTAK63 exhibit a long-term (at least until 6 months) polyfunctional Th1/Th17 response in the draining lymph nodes and in the lungs. This response was accompanied by the increased presence of a diverse set of memory T cells, including central memory, effector memory and tissue-resident memory T cells. After the challenge, the T cell phenotype in the lymph nodes and lungs were characterized by a decrease in central memory T cells, and an increase in effector memory T cells and effector T cells. More importantly, when challenged 6 months after the immunization, this group demonstrated increased protection in comparison to BCG.In conclusion, this work provides experimental evidence in mice that the rBCG-LTAK63 vaccine induces a persistent increase in memory and effector T cell numbers until at least 6 months after immunization, which correlates with increased protection against Mtb. This improved immune response may contribute to enhance the long-term protection.